1999
DOI: 10.1111/j.1447-0756.1999.tb01142.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Physical Abuse during Pregnancy GMCH, Nagpur, India

Abstract: There is significant physical abuse during pregnancy in central India. Routine screen by AAS and a cohort study looking at adverse outcome of pregnancy is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 16 publications
4
48
1
1
Order By: Relevance
“…Similar observations were also reported from around the world that antenatal care was much higher where the women were not facing domestic abuse while the antenatal care seems less where such incidence was found (Purwar et al, 1999). As far as adequate food and rest to the pregnant women was concerned, significant association was reported where women facing any form of violence compare to the women who were not facing violence (Kajsa et al, 2003).…”
Section: Discussionsupporting
confidence: 77%
“…Similar observations were also reported from around the world that antenatal care was much higher where the women were not facing domestic abuse while the antenatal care seems less where such incidence was found (Purwar et al, 1999). As far as adequate food and rest to the pregnant women was concerned, significant association was reported where women facing any form of violence compare to the women who were not facing violence (Kajsa et al, 2003).…”
Section: Discussionsupporting
confidence: 77%
“…Abused women were more likely to be: Buddhist; of greater parity with an unwanted pregnancy; dwelling in slums; from an extended family. Low level of education and stress of husband were also factors (Purwar et al 1999).…”
Section: Prevalence and Nature Of Violencementioning
confidence: 99%
“…As to the severity of violence, 4.5% of abused women required hospitalisation; 3.8% needed medical assistance and 19.7% women were afraid of their partner. Abused women were likely to begin antenatal care aft er 32 weeks ' gestation (Purwar et al 1999).…”
Section: Pregnancy Outcome and Infant Mortalitymentioning
confidence: 99%
“…For example, 22% of women attending an antenatal clinic in central India reported physical violence (Purwar et al, 1999). Men also acknowledge the relatively high prevalence of IPV; thus, a study conducted in five districts in northern India reported that 5.4−13% of their sample (n = 1990) acknowledged assaulting their wives during pregnancy (Martin et al, 1999).…”
Section: Introductionmentioning
confidence: 99%